(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
In 2020, India unveiled its New Education Policy (NEP), signaling a monumental shift in the nation’s approach to education. Coming after more than three decades since the last policy framework was laid out, the NEP aims to meet the changing dynamics of the socio-economic environment, technological advancements, and global best practices in the domain of education. Intending to rejuvenate the nation’s educational structure, the policy reflects a blend of tradition with modernity, guiding the country’s youth towards a future resonant with the ideals of a global citizen yet deeply rooted in Indian ethos.